2014
DOI: 10.1161/strokeaha.113.003605
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute and Persisting Ischemic Brain Lesions in Patients Randomized to Carotid Stenting or Endarterectomy

Abstract: In the MRI substudy of the International Carotid Stenting Study (ICSS), acute ischemic brain lesions on diffusion-weighted imaging (DWI) were found more often after stenting than after endarterectomy.1,2 We investigated risk factors for acute periprocedural brain lesions and lesions persisting on follow-up imaging. MethodsMRI was performed 1 to 7 days before (pretreatment scan), 1 to 3 days after (early post-treatment scan), and 27 to 33 days after treatment (follow-up scan, performed in 6 of 7 centers) among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…In the International Carotid Stenting Study trial, authors showed lower incidence of brain lesions in females than males. 22 In our material, perioperative neurologic complications were doubled in females. It is difficult to make any conclusion without any metaeanalysis; while in the meantime, female patients should be informed about possible increased risks although careful selection of asymptomatic female patients could contribute to better results in this group.…”
Section: Discussionmentioning
confidence: 71%
“…In the International Carotid Stenting Study trial, authors showed lower incidence of brain lesions in females than males. 22 In our material, perioperative neurologic complications were doubled in females. It is difficult to make any conclusion without any metaeanalysis; while in the meantime, female patients should be informed about possible increased risks although careful selection of asymptomatic female patients could contribute to better results in this group.…”
Section: Discussionmentioning
confidence: 71%
“…Human umbilical vein endothelial cells (HUVEC) from Lonza [26] were cultivated in EGM Bullet Kit medium (Lonza).…”
Section: Methodsmentioning
confidence: 99%
“…In the MRI sub-study, CAS was associated with more acute and persisting ischemic brain lesions. 237 Peri-procedural hemodynamic instability, including bradycardia, asystole, or hypotension requiring treatment, were more likely to cause ischemic brain lesions in CAS patients versus CEA patients (RR, 3.36; 95% CI: 1.73–6.50). 238 …”
Section: Interventional Managementmentioning
confidence: 98%